Consumer's Attitude Towards Retrofitting of Existing Internal Combustion Engine Scooters with Electric Conversion Kit in India - Agarwal, A. K; Babbar, Shantam (Journal of Commerce and Trade, 2022)
Increasing Pollution has made the World to find new sources of renewable energy. Electric vehicles are gaining momentum in this fanfare. As a result, Electric Conversion Kit has emerged as a new concept as a replacement to the traditional fuel-based vehicles. This paper projects the consumer's attitude relating to adoption of Electric Conversion Kits in their fuel-based vehicles in India. The present study is based on primary data which is collected from urban commuters. The paper highlights the consumer awareness as to the electric scooters, electric conversion kits for their fuel-based scooters and predict their willingness to switch towards e-mobility in future. Further, the paper brings a comparison between the consumers likeliness to adopt electric conversion kits over the purchase of an all-new electric scooter. The paper also depicts an analysis of future adoption of e-mobility based on the average daily run which may help in deciding the tentative battery size needed by the consumer to commute in a hazel free manner. The companies and government together need to spread awareness among the inhabitants about this concept and its likely benefits to environment as well as buyers in their lives. Also, there is a need to set a positive environment as to safety of these kits in order to fetch the public reliance. Classification-JEL: M13